2021
DOI: 10.21203/rs.3.rs-69131/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A telephone assessment and advice service within an ED Physiotherapy clinic: A single-site quality improvement cohort study

Abstract: BackgroundIn response to issues with timely access and high non-attendance rates for Emergency Department (ED) physiotherapy, a telephone assessment and advice service was evaluated as part of a quality improvement project. This telehealth option requires minimal resources, with the added benefit of allowing the healthcare professional streamline care. A primary aim was to investigate whether this service model can reduce wait times and non-attendance rates, compared to usual care. A secondary aim was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…At the Queens Hospital Burton site of the University Hospitals of Derby and Burton National Health Service (NHS), the MSK physiotherapy department observed a high rate of failed attendances from patients referred from the emergency department, recording 14.4% of initial appointments not being attended by patients. These findings were not uncommon and were similar to the aforementioned studies [6,10,11].…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…At the Queens Hospital Burton site of the University Hospitals of Derby and Burton National Health Service (NHS), the MSK physiotherapy department observed a high rate of failed attendances from patients referred from the emergency department, recording 14.4% of initial appointments not being attended by patients. These findings were not uncommon and were similar to the aforementioned studies [6,10,11].…”
Section: Introductionsupporting
confidence: 90%
“…A senior physiotherapist was utilized to provide self-management and advice for each of the conditions. Although the study used a small sample size, the researchers concluded the service reduced waiting times and was accepted by service users [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations